The Pathfinder; Or, The Inland Sea - Cooper, James Fenimore, 1789-1851 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Pathfinder; Or, The Inland Sea" by James Fenimore Cooper is a historical novel published in 1840. The fourth book featuring frontier hero Natty Bumppo, it follows the Pathfinder as he guides a young woman through dangerous wilderness around Lake Ontario. For the first time in the series, Natty experiences romantic love when he falls for nineteen-year-old Mabel Dunham. This tests his simple, honest nature as he faces the tension between domestic life and his true home in the wild. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Pathfinder,_or_The_Inland_Sea
Release date is 1999-09-01
Produced by Nigel Lacey, and David Widger
Keywords: Historical fiction; Indians of North America -- Fiction; War stories; United States -- History -- French and Indian War, 1754-1763 -- Fiction; Love stories; Frontier and pioneer life -- Fiction; Bumppo, Natty (Fictitious character) -- Fiction; Ontario, Lake (N.Y. and Ont.) -- Fiction